PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN APLIKASI LECTORA INSPIRE PADA PEMBELAJARAN IPA UNTUK KELAS V SEKOLAH DASAR - Nadila; Vika Martahayu; Erika Fitri Wardani (JBES (Journal Basic Education Skills), 2025)
This research was motivated by students' boredom in learning activities, necessitating engaging learning media that align with the current technological era, namely the 4.0 industrial revolution, or in other words, digital-based learning. This study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were fifth-grade students of SD Negeri 12 Muntok. The development of interactive multimedia using the Lectora Inspire application for science learning in fifth-grade elementary school aimed to produce valid, practical, and effective learning media. The validity of the product was assessed through validation by media experts (70%, valid category), content experts (100%, highly valid), and language experts (96%, highly valid). Practicality was evaluated through a small-scale trial (5 students, 96%, highly practical), a large- scale trial (20 students, 86%, highly practical), and teacher assessment (97.5%, highly practical). The effectiveness of the product was demonstrated through pre-test and post-test analyses, which showed a significant improvement in students’ understanding after using the multimedia. Interactive features such as animations, simulations, and practice questions made the material more engaging and easier to understand. Based on validation and trial results, this interactive multimedia was deemed highly valid, highly practical, and effective in enhancing science learning outcomes for fifth-grade elementary students. This media offers an innovative solution to support a more interactive and effective learning process.